Influence of foliar application with putrescine, salicylic, and ascorbic acid on the productivity and physical and chemical fruit properties of Picual olive trees - Laila F. Hagagg; Nazmy Abd-Alhamid; Hassan S. A. Hassan; Ahmed M. Hassan; Esmail A. E. Geanidy (Bulletin of the National Research Centre, 2020)
Abstract Background and objective Olive tree is very popular in the Mediterranean area because of its fruits and oil yields. Both of them are worldwide known by their beneficial health properties. Salicylic acid is naturally occurring as phenolic compound and endogenously synthesized as signaling molecule in plants and influences various physiological and biochemical functions in plants. Ascorbic acid is an antioxidant molecule and a key substrate for the detoxification of ROS. Putrescine participates in several processes of plant growth and development. Putrescine participates in several processes of plant growth and development. Therefore, the objective of this study is to determine the best concentrations of these substances to improve olive fruits yield and its chemical and physical properties. Materials and methods The field experiment was conducted during two seasons of 2017 and 2018 on adult olive trees of Picual cv. (8 years old) in a private orchard located in Ismailia Governorate, Egypt, to study the effect of foliar application with different concentrations of putrescine, salicylic, and ascorbic, in two dates of November and December. The effect of different concentrations and dates of spray under the conditions of the saline irrigation water (4.40 ds m−1) were evaluated on the fruit yield, fruit physical characteristics and fruit chemical properties of olive trees of Picual cv. Results In this study, all treatments were able to improve all studied characters compared with the control treatment in both spraying dates of November and December in both seasons, respectively. Moreover, the best yield of olive fruits in this study was recorded with the application of putrescine at 15 ppm + salicylic at 200 ppm + ascorbic at 2000 ppm in the first and second seasons, respectively. Conclusion Spraying Picual olive trees with putrescine, salicylic, and ascorbic acid in this study under the conditions of the saline irrigation water (4.40 ds m−1) was able to improve fruit yield and fruit physical and chemical properties of olive trees of Picual cv. compared with the control treatment in both spraying dates